2014
DOI: 10.1186/1742-4690-11-1
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral Nef suppresses iron uptake in a strain specific manner through inhibition of Transferrin endocytosis

Abstract: BackgroundIncreased cellular iron levels are associated with high mortality in HIV-1 infection. Moreover iron is an important cofactor for viral replication, raising the question whether highly divergent lentiviruses actively modulate iron homeostasis. Here, we evaluated the effect on cellular iron uptake upon expression of the accessory protein Nef from different lentiviral strains.ResultsSurface Transferrin receptor (TfR) levels are unaffected by Nef proteins of HIV-1 and its simian precursors but elevated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 50 publications
7
57
0
Order By: Relevance
“…In contrast, interaction of Nef with ␤-COP was weak and nonconserved, and of note, only HIV-1 NA7 and NL4-3 Nef bound to ACOT8. In agreement with previous data (19), HIV-2-and simian immunodeficiency virus (SIV)-derived Nef proteins potently interacted with AP-2 ( Fig. 2), most likely due to the presence of tyrosine-based AP-2 binding motifs, which are absent in HIV-1 and SIVcpz Nefs (15).…”
supporting
confidence: 91%
“…In contrast, interaction of Nef with ␤-COP was weak and nonconserved, and of note, only HIV-1 NA7 and NL4-3 Nef bound to ACOT8. In agreement with previous data (19), HIV-2-and simian immunodeficiency virus (SIV)-derived Nef proteins potently interacted with AP-2 ( Fig. 2), most likely due to the presence of tyrosine-based AP-2 binding motifs, which are absent in HIV-1 and SIVcpz Nefs (15).…”
supporting
confidence: 91%
“…However, one recent study suggested that the effect of Nef on TfR1 may be strain specific. 32 The increased cellular iron levels observed in our studies may be a consequence of virus attempting to establish a favorable environment for its own replication. As tissue iron accumulation is seen in many HIV-associated diseases, including neurodegeneration and diastolic cardiac dysfunction, [33][34][35][36][37] it is tempting to speculate that altered cellular iron homeostasis secondary to HIV infection may, at least partially, contribute to the organ damage associated with HIV infection.…”
Section: Relationship Among Iron Hiv and Art 309mentioning
confidence: 76%
“…1D and E). This included previously described targets such as CXCR4 (CD184) and MHC-I receptors but also transferrin receptor (CD71), which was reported to be downregulated by Nef in an allele-and cell typedependent manner (69)(70)(71). In addition, a number of new targets with potentially interesting links to HIV biology were identified, such as CD37, Lamp-1 (CD107a), Lamp-2 (CD107b), ICAM-1 (CD102), or gamma interferon receptor (CD119).…”
Section: Resultsmentioning
confidence: 99%